Treatises on Noah and David - Ambrosius, Mediolanensis, Heiliger 339-397 (The fathers of the church, 2020)
"There are three treatises in this book: one on Noah and two on King David. St. Ambrose offers an interpretation of the story of Noah (Genesis 6:5 through 9:29) and two essays on the story of King David's adultery with Bathsheba and his order for her husband to be killed (2 Samuel 11:2 through 12:25). His exegesis of the narrative of Noah and the Flood is allegorical. With regard to David and Bathsheba, Ambrose includes his own commentary on Psalm 51 (50 in the Septuagint), which he interprets as David's heartfelt repentance. Ambrose's overall purpose in the two treatises on David is to defend him as a righteous man"--